The Subject and the Real: Ethical Implications of A. Badiou’s Philosophy - Pocius, Kasparas (Problemos, 2019)
Alain Badiou’s theory of ethics of the subject implies that the individual interpellation of the symbolic plane could be secondary to the truth process, which grounds the formation of the subject. We arrive at the hypothesis that the subject of the interpellation is already a subject of truth when the symbolic interpellation process starts.In the paper, two contemporary ethical orientations are emphasized: democratic materialism, which comprises the idealism created by market laws, and a materialist dialectic, which opens the possibility of the subject’s formation during the struggles. However, Badiou’s attempts to create an alternative symbolic plane – a historical plane – do not seem reassuring; therefore, one must look at the event-producing-history from the psychoanalytical perspective.The theory of drives opens the possibility to relate Badiou’s subject to the repressed real, to show him as immune to the desire, which may be derived from a symbolical plane, and able to ground his struggles with revolutionary jouissance while not allowing history to end too early.
Keywords: Alain Badiou; the subject; interpellation; the Real; drive